Agamben’s Entwicklungsfähigkeit: Review of Carlo Salzani, Agamben and the Animal - Kotsko, Adam (Humanimalia, 2022)
Review of Carlo Salzani, Agamben and the Animal (Newcastle upon Tyne: Cambridge Scholars Publishing, 2022)